Pest control in paddy field: practices in Rantau Panjang - Siti Nur Syafinah Abdul Nasir (2014)
Practices to control pest outbreaks in paddy field are needed to prevent severe damage and lower total of yield.This project presents the studies of practices used to control pest infestation in paddy field in Rantau Panjang Kelantan.This research is function in collecting data by conducting a preliminary survey to identify the practices used to control pest attacks used by farmers in Rantau panjang Kelantan. Data obtained were analyzed using Statistical package for the Social Science (SPSS) and descriptive analysis. Preferably, most of farmers using chemical practice to control the infestation. The types of pest that attacks Rantau Panjang paddy fields were identified to be stem borer (Scirpophaga incerarrulas), leaf folder (Cnaphalocrocis medinalis), case worm (Nymphula depuntalis), army worm (Spodoptera mauritia) and apple snail (Pomacea spp.).Collected data can be use as baseline data in future study as a references in pest control management in paddy field.